The first industrialists : the problem of origins - Crouzet, François, 1922-2010 (Cambridge : Cambridge university press, 1985)
The 'first industrialists' were the pioneers and leaders of the British industrial Revolution, the men who founded factories and other large establishments, which were typical of the new economic system. They had a number of precursors since the sixteenth century, but, on the whole, they were a new breed, which emerged in the late eighteenth century. They were markedly different from the leaders of traditional industry. This book is focused on the social and occupational origins of those founders of modem British industry: what kind of families did they come from? What was their occupation before they set up as industrialists? In discussing these and other issues, this study (based on Professor Crouzet's 1983 Ellen McArthur Lectures) Aiakes an important contribution to the problem of social mobility during the Industrial Revolution.
Bibliografische referenties ; index
Keywords: Industrialists -- History -- 18th century. -- Great Britain; Industries -- History -- 18th century. -- Great Britain